2022
DOI: 10.1093/mollus/eyac018
|View full text |Cite
|
Sign up to set email alerts
|

Response of optic gland pathways to thermal stress in the reproductive phase of female Octopus maya

Abstract: The octopus optic glands are the source of multiple signalling molecules that control the transitions through different physiological stages, such as maturation, ageing and death. This study focused on the role of the optic glands during the reproductive phase of Octopus maya, investigating the molecular mechanisms that prevent reproduction at elevated temperatures. RNA sequencing was used to analyse and compare optic gland transcriptomic profiles of female O. maya before, during and after egg-laying under opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…Despite the additional effects that provoke high temperature on the ovary of O. maya females are still not known, possibly, a heart energetically limited by the high temperature may also produce limitations in pumping oxygenated hemolymph, consequently, in oxygen transport to tissues to satisfy the energetic demands that occur in the ovary and oviductal gland – two critical organs involved in the octopus reproduction ( Domínguez-Estrada et al, 2022 ; Juárez et al, 2022 ; Olivares et al, 2017 ). In this sense, a question arises: How would the systemic heart mitochondria control reproduction in octopus?…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the additional effects that provoke high temperature on the ovary of O. maya females are still not known, possibly, a heart energetically limited by the high temperature may also produce limitations in pumping oxygenated hemolymph, consequently, in oxygen transport to tissues to satisfy the energetic demands that occur in the ovary and oviductal gland – two critical organs involved in the octopus reproduction ( Domínguez-Estrada et al, 2022 ; Juárez et al, 2022 ; Olivares et al, 2017 ). In this sense, a question arises: How would the systemic heart mitochondria control reproduction in octopus?…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, thermally stressed females spawn, even when embryos are at thermal risk. However, the results obtained in the laboratory have demonstrated that in temperatures higher than 27°C, the octopus spawn is inhibited, suggesting that other more complex processes regulate O. maya reproduction during thermal stress ( Di Cosmo and Polese, 2014 ; Domínguez-Estrada et al, 2022 ; Juárez et al, 2015 , 2019 ; Ventura-López et al, 2022 ). Considering the previous results, a second question arises: Could the strength of the oxygen flow pumped from the systemic heart be the signal to the brain that triggers the complex regulatory mechanisms directed to preserve the embryos’ integrity, inhibiting spawning at high temperatures?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, during the spawning stage, octopuses stop feeding while focusing exclusively on laying and caring for eggs (Anderson et al, 2002). During this period of no or less feeding, octopuses rely on energy in the form of adenosine triphosphate (ATP) from body reserves (Domínguez-Estrada et al, 2022). Because an excessive amount of ATP is required throughout the brooding period, their muscles deteriorate and animals become physically less active, hence unable to hunt (Meza-Buendía et al, 2021).…”
Section: Discussionmentioning
confidence: 99%